Exploring culturally-informed representations of trauma among refugee victims of torture in Athens, Greece - Womersley, Gail (My University, 2018)
The mental health impact of atrocities endured by refugees and asylum seekers is clear, with significantly high prevalence rates of post-traumatic stress disorder (PTSD) being reported among this population. Torture has emerged as a particular triggering factor. However, there have been significant concerns raised in the literature over the relevance and cross-cultural validity of this psychiatric diagnosis for refugee populations. Moreover, scholars globally have argued that the location of trauma at the level of the individual in the form of a PTSD diagnosis neglects the broader socio-political and cultural context within which trauma manifests. In order to explore culturally informed representations and perspectives on trauma among refugee victims of torture, we present the results of 12 months of research among asylum seekers and refugees in a center for victims of torture in Athens. This research includes 125 in-depth, qualitative interviews with beneficiaries (refugee victims of torture), health professionals, cultural mediators/interpreters, and leaders from refugee associations and communities across Athens. The results are illustrated using case studies. The majority of refugee victims of torture appear to contest the medicalised notion of « PTSD » with which they had been diagnosed. When referring to their subjective experiences of trauma, they draw upon a variety of diverse cultural representations of suffering (« explanatory models ») and idioms of distress to explain their subjective experiences of trauma. The research findings highlight the need for psychosocial interventions to incorporate a more culturally contextualised understanding of trauma.
, IACPP: The 24th Congress of the International Association for Cross-Cultural Psychology, Guelph, Canada